(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
Suwarno (2010) Population dynamic of the swallowtail butterfly, Papilio polytes (Lepidoptera: Papilionidae) in dry and wet seasons. Biodiversitas 11: 19-23. The population dynamic of Papilio polytes L. (Lepidoptera: Papilionidae) in dry and wet seasons was investigated in the citrus orchard in Tasek Gelugor, Pulau Pinang, Malaysia. Population of immature stages of P. polytes was observed alternate day from January to March 2006 (dry season, DS), from April to July 2006 (secondary wet season, SWS), and from October to December 2006 (primary wet season, PWS). The population dynamics of the immature stages of P. polytes varied between seasons. The immature stages of P. polytes are more abundance and significantly different in the PWS than those of the DS and the SWS. The larval densities in all seasons decreased with progressive development of the instar stages. Predators and parasitoids are the main factor in regulating the population abundance of immature stages of P. polytes. There were positive correlations between the abundance of immature stages of P. polytes and their natural enemies abundance in each season. Ooencyrtus papilioni Ashmead (Hymenoptera: Encyrtidae) is the most egg parasitoid. Oxyopes quadrifasciatus L. Koch. and O. elegans L. Koch. (Araneae: Oxyopidae) are the main predators in the young larvae, meanwhile Sycanus dichotomus Stal. (Heteroptera: Reduviidae), Calotes versicolor Fitzinger (Squamata: Agamidae), birds and praying mantis attacked the older larvae. Key words: population dynamic, seasons, Papilio polytes, immature stages, natural enemies.